Which linguistic resources for the teaching / learning of French as a foreign language? - Mechri Bendaoud Bendaoud (Journal of Science and Knowledge Horizons, 2023)
This study is truly intended to be a contribution inscribed in a scrupulously didactic context, hence the idea of teaching – learning French as a foreign language in an Algerian context. Our attention is mainly vocalized on the attitude of the learner and his previous achievements in terms of FLE in the secondary cycle. However, it is therefore appropriate to specify from any language task, i.e. the written expression considered as the outcome of any learning from a didactic point of view, the exploitation of its achievements according to a theme whose concept of instruction is already present in all the linguistic-didactic elements supposed to allow him to reorganize his thought and give him the very meaning of a methodology as a common thread from which he can easily take action, this will doubly reflect his ability to acquisition and understanding of the linguistic concept initially implemented from the textual approach. In this sense, we question the fact of believing that the appropriation of such a linguistic notion can no longer be confined to its classic formulation: linguistics and didactics of languages, in particular FLE in an Algerian context. Questioning the different parameters likely to make access to knowledge in French as a foreign language a plausible case, this amounts to asking ourselves about the basic knowledge of the learner and the methods that will allow him to carry out a task; either a language production for which it is advisable to define the strategy engaged and the linguistic resources acquired as the main lever of a mediation, hence the idea of the contribution of linguistics to the teaching of French as a foreign language and the methodological orientations which under -tend the comprehension of the relational lexicon as proof of a use that one can judge satisfactory of the entity FLE in the school circles.